Kemungkinan sebaran zirkon pada endapan placer di Pulau Kalimantan - Danny Zulkifli Herman (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no2.20073Most alluvium with valued heavy minerals originated from regions of continental shelf, from which recycle process for stable minerals play an important role in transportation and final concentration formation of the minerals. Kalimantan Island as part of continental shelf has a great opportunity to provide condition or environment for placer deposition with zircon content due to: comprising particularly basement rock of calc-alkali to alkali series (granite, granodiorite, tonalite and monzonite) which were suggested as the main supplier sources of zircon; having a long period of regional stability as main contribution in continuation processes of weathering, transportation and forming deposition environment of alluvium and located within a tropical climate with high humidity from which mechanical and chemical weathering processes play an important role in releasing zircon from its source rocks. Continental placer deposit of fluvial sub-environment category is suggested to have possibility to form deposition zone lying between the mountains and the seas, reaching over wide areas and forming huge volume reservoirs with content of zircon. Based on zircon identification (associated with gold or diamond) of placer pan concentrates at some areas of West Kalimantan and Central Kalimantan, these have proved how widespread of zircon deposition within fluvial sub-environments in both regions. This important information inspires an opportunity to do exploration of placer zircon deposits within fluvial sub-environments in entirely Kalimantan Island, without neglecting to the transition placer of strandline sub-environment category and marine environment which enable to have an economic deposit of zircon.